Patch-Clamp Analysis of the Mitochondrial H+ Leak in Brown and Beige Fat - Bertholet, Ambre M.; Kirichok, Yuriy (Frontiers in Physiology, 2020)
Mitochondria convert the chemical energy of metabolic substrates into adenosine triphosphate (ATP) and heat. Although ATP production has become a focal point of research in bioenergetics, mitochondrial thermogenesis is also crucial for energy metabolism. Mitochondria generate heat due to H+ leak across the inner mitochondrial membrane (IMM) which is mediated by mitochondrial uncoupling proteins. The mitochondrial H+ leak was first identified, and studied for many decades, using mitochondrial respiration technique. Unfortunately, this method measures H+ leak indirectly, and its precision is insufficient for the rigorous insight into the mitochondrial function at the molecular level. Direct patch-clamp recording of H+ leak would have a significantly higher amplitude and time resolution, but application of the patch-clamp technique to a small subcellular organelle such as mitochondria has been challenging. We developed a method that facilitates patch-clamp recording from the whole IMM, enabling the direct measurement of small H+ leak currents via uncoupling proteins and thus, providing a rigorous understanding of the molecular mechanisms involved. In this paper we cover the methodology of measuring the H+ leak in mitochondria of specialized thermogenic tissues brown and beige fat.